Exosomal coactivator-associated arginine methyltransferase 1 derived from adipocytes accelerates diabetic wound healing by modulating inflammation and promoting angiogenesis - Zhang, Yongxiang; Pan, Yao; Yang, Kai; Wu, Xiansun; Zhang, Yaoyao; Xu, Fengbiao; Di, Tietao; Liu, Wang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionDelayed wound healing remains a significant clinical challenge under diabetic conditions, characterized by chronic inflammation and impaired angiogenesis. Traditional treatments show limited efficacy, highlighting the urgent need for innovative therapeutic approaches.MethodsThis study investigated the therapeutic potential of exosomes derived from subcutaneous adipocytes (Adipo-EVs) using a diabetic mouse model. Adipo-EVs were locally administered to full-thickness wounds, and healing efficiency was evaluated through wound closure kinetics, histopathology (H&E, Masson’s trichrome), immunohistochemistry (Ki67,α-SMA), and molecular analysis (qPCR, proteomics). The role of the enriched protein Carm1 was validated via siRNA knockdown in vitro and in vivo.ResultsAdipo-EVs significantly accelerated wound closure, increased cellular proliferation, enhanced collagen deposition, and improved myofibroblast differentiation. Mechanistically, Adipo-EVs suppressed pro-inflammatory cytokines (IL-6, TNF-α) while upregulating IL-10 and promoting angiogenesis (elevated CD31+ vessels and in vitro tube formation). Proteomic analysis identified Carm1 as a highly enriched mediator in Adipo-EVs. Knockdown of Carm1 abolished the anti-inflammatory and angiogenic effects of Adipo-EVs, leading to impaired wound repair.DiscussionOur findings demonstrate that exosomal Carm1 critically modulates inflammation and angiogenesis to enhance diabetic wound healing. This study reveals Carm1 as a pivotal therapeutic component of adipocyte-derived exosomes, offering a novel strategy for managing chronic diabetic wounds.